Häufigkeit postinfektiöser Kälteagglutinine bei Infektionen mit Mycoplasma pneumoniae, Varicella-Zoster- und Rubellaviren - Leo, Albrecht; Enders, Gisela; Roelcke, Dieter (Beiträge zur Infusionstherapie und Transfusionsmedizin, 1994)
Cold agglutinins (CA) are observed during acute infections as transiently occurring postinfection autoantibodies directed against erythrocyte antigens. Distinct infectious agents induce CA of distinct specificity. A common association is the infection with Mycoplasma pneumoniae and the production of CA with anti-I specificity. In infections with varicella-zoster virus (VZV) and rubella virus (RV) a few cases of CA appearance are reported, all of them showing specificity for the Pr antigens. We examined the frequency of CA with the anti-Pr specificity in patients suffering from acute infections with VZV and RV (table 1). The known association of anti-I in about 70% of the cases with acute Mycoplasma pneumoniae infection is confirmed by our results. The occurrence of CA in infections with VZV and RV is a rare event. Based on published data, the specificity of these CA apparently is anti-Pr. Three of 5 anti-Pr examples were found in newborns with rubella embryopathy. Possibly, anti-Pr can be observed more frequently in these patients compared to adults.